Demonstrator av flöde i en tre-fas motor/ Demonstrator of flow in a three-phase motor - Amer, Malek; Mohamed, Abshir (My University, 2023)
Abstract This degree project was carried out at school in the spring of 2023. The purpose of this project was to create a demonstrator in the form of an application that would show how the magnetic field moves in a rotating induction motor. This project idea is not too popular in the market, thus there is much room for potential development in this field. Even though the field movement in an electric motor has been studied carefully, it can be difficult to illustrate what it actually looks like in operation in real-time. That’s where this solution comes into the picture. The project can be a tool for developing the educational aspect of this specific subject. It also makes it generally easier to study an electric machine and its characteristics. The project use hall effect sensors as they measure magnetic field. They were connected to an Arduino that handles the measurements and then sends them via Bluetooth to the application. The application was programmed in Android Studio using the Java language. How the field would be illustrated in the application was a decision process that changed during the work. This was because it took more time than anticipated, which changed what could be implemented. The magnetic field generated by the windings is presented as a circle at each winding that changes in size based on the value of the field. Each sensor will lie on a different winding to measure the change in the field. The circles are used because they can clearly show increased positive field by expanding and decreased negative field by decreasing. Since the field rotates in the motor, the positive and negative parts will also rotate, and this will show different sizes of field at different time points. The goal was to show it in a way that was easiest to understand with the existing time. The work resulted in a well-functioning application with small delays. The application can improve its performance but also with more features. Most time in the work was spent on getting the values from the Arduino to the application and separating the string that the values are in when they are sent over.